2014
DOI: 10.1089/dna.2013.2217
|View full text |Cite
|
Sign up to set email alerts
|

A-1012G Promoter Polymorphism of Vitamin D Receptor Gene Is Associated with Psoriasis Risk and Lower Allele-Specific Expression

Abstract: Psoriasis is caused by a combination of genetic, immunologic, and environmental factors. The vitamin D receptor (VDR) is involved in antiproliferative and prodifferentiation pathways in keratinocytes and exerts immunosuppressive effects. We aimed to investigate possible associations between VDR polymorphisms and psoriasis susceptibility and to evaluate functional effects of potential psoriasis-associated polymorphisms. We genotyped 108 patients with psoriasis and 268 healthy controls at 5 VDR polymorphisms (A-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 39 publications
5
30
0
1
Order By: Relevance
“…Several studies have identified an association between VDR polymorphisms and psoriasis susceptibility. [49][50][51] We have analyzed the polymorphisms of VDR gene and psoriasis susceptibility and we have found that in our population the A-1012G promoter polymorphism of the VDR gene is associated with psoriasis risk and the mRNA of VDR in this polymorphism is lower expressed, favoring the conditions that may alter cutaneous barrier and the development of psoriatic lesions. 51 Our group has studied the immunohistochemical expression of VDR, claudin-1, occludin and Zonulin-1 (ZO-1), demonstrating that psoriatic skin has a decreased expression of VDR and tight-junction proteins and that there is a correlation between the expression of VDR, claudin-1 and ZO-1, demonstrating that probably this micronutrient may preserve the cutaneous integrity ( Fig.…”
Section: Barrier Organsmentioning
confidence: 84%
See 1 more Smart Citation
“…Several studies have identified an association between VDR polymorphisms and psoriasis susceptibility. [49][50][51] We have analyzed the polymorphisms of VDR gene and psoriasis susceptibility and we have found that in our population the A-1012G promoter polymorphism of the VDR gene is associated with psoriasis risk and the mRNA of VDR in this polymorphism is lower expressed, favoring the conditions that may alter cutaneous barrier and the development of psoriatic lesions. 51 Our group has studied the immunohistochemical expression of VDR, claudin-1, occludin and Zonulin-1 (ZO-1), demonstrating that psoriatic skin has a decreased expression of VDR and tight-junction proteins and that there is a correlation between the expression of VDR, claudin-1 and ZO-1, demonstrating that probably this micronutrient may preserve the cutaneous integrity ( Fig.…”
Section: Barrier Organsmentioning
confidence: 84%
“…Several studies have identified an association between VDR polymorphisms and psoriasis susceptibility . We have analyzed the polymorphisms of VDR gene and psoriasis susceptibility and we have found that in our population the A‐1012G promoter polymorphism of the VDR gene is associated with psoriasis risk and the mRNA of VDR in this polymorphism is lower expressed, favoring the conditions that may alter cutaneous barrier and the development of psoriatic lesions …”
Section: Barrier Organsmentioning
confidence: 99%
“…Richetta et al [89] showed that among 5 common VDR polymorphisms (A-1012G, FokI, BsmI, ApaI, and TaqI), the A-1021G polymorphism is associated with the risk of psoriasis in an Italian population. In another study, ApaI and a specific haplotype of 5 VDR polymorphisms were associated with the risk of psoriasis in a Chinese population [90].…”
Section: Role Of Vitamin D In Certain Inflammatory Skin Diseasesmentioning
confidence: 99%
“…Several studies identified an association between polymorphisms of vitamin D receptor ( VDR ) and psoriasis susceptibility [9]. Richetta et al, have found that the A-1012G promoter polymorphism of the VDR gene is associated with psoriasis risk through a lower expression of VDR mRNA, favoring conditions that may alter cutaneous barrier and the development of psoriatic lesions [31]. In addition, in psoriatic skin a decreased expression of VDR and reduced tight-junction proteins is associated [32].…”
Section: The Dermatologist’s Point Of Viewmentioning
confidence: 99%